2020
DOI: 10.1111/anae.15163
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and trial sequential analysis of intravenous vs. oral peri‐operative paracetamol

Abstract: Summary Postoperative pain might be different after intravenous vs. oral paracetamol. We systematically reviewed randomised controlled trials in patients >15 years that compared intravenous with oral paracetamol for postoperative pain. We identified 14 trials with 1695 participants. There was inconclusive evidence for an effect of route of paracetamol administration on postoperative pain at 0–2 h (734 participants), 2–6 h (766 participants), 6–24 h (1115 participants) and >24 h (248 participants), with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…Intravenous paracetamol produces peak plasma concentrations in approximately 15 min compared to 45–50 min following oral administration, resulting, theoretically, in a faster onset of the analgesic effect (5 min) [ 31 , 32 ]. However, several studies, demonstrate similar analgesic efficacy of intravenous and oral preparations [ 31 , 32 , 33 , 34 , 35 , 36 ]. In a double-blind RCT, a heterogeneous group of 87 patients of the Emergency Department with moderate-to-severe pain (median age of 45 years, 60% females) were randomized to receive 1 g of paracetamol either intravenously or orally; the changes in Visual Analogue Score (VAS) for pain from baseline (67.9 ± 16.0 mm) to 30 min post-administration outcome did not differ between groups (−16.0 ± 19.1 mm in the intravenous group and −14.6 ± 26.4 in the oral group, p = 0.79) [ 33 ].…”
Section: Paracetamolmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous paracetamol produces peak plasma concentrations in approximately 15 min compared to 45–50 min following oral administration, resulting, theoretically, in a faster onset of the analgesic effect (5 min) [ 31 , 32 ]. However, several studies, demonstrate similar analgesic efficacy of intravenous and oral preparations [ 31 , 32 , 33 , 34 , 35 , 36 ]. In a double-blind RCT, a heterogeneous group of 87 patients of the Emergency Department with moderate-to-severe pain (median age of 45 years, 60% females) were randomized to receive 1 g of paracetamol either intravenously or orally; the changes in Visual Analogue Score (VAS) for pain from baseline (67.9 ± 16.0 mm) to 30 min post-administration outcome did not differ between groups (−16.0 ± 19.1 mm in the intravenous group and −14.6 ± 26.4 in the oral group, p = 0.79) [ 33 ].…”
Section: Paracetamolmentioning
confidence: 99%
“…In a meta-analysis of six RCTs comparing intravenous versus oral administration, Jibril et al found no evidence indicating that the increased bioavailability of the intravenous preparations produces a superior analgesia [ 31 ]. In a recent systematic review of 14 trials with 1695 participants on postoperative pain, there was no significant difference between intravenous and oral paracetamol in terms of pain intensity up to >24 postoperative h [ 36 ].…”
Section: Paracetamolmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Given cost concerns and lack of proven data to demonstrate a difference in efficacy, we chose to use the oral route for administration. 26 Acetaminophen was then administered postoperatively as needed to provide ongoing analgesia with additional ibuprofen available for break-through pain. 27 One concern with the preoperative administration of oral medications may be the volume of fluid required in the digestive tract to absorb the medication in a patient who is being kept nil per os (NPO).…”
Section: Dovepressmentioning
confidence: 99%
“…Regarding the clinical application of acetaminophen, it remains unclear whether its analgesic effect varies depending on the route of administration. Raffa et al reported that the analgesic effect of intravenous acetaminophen was superior to that of oral and rectal administration, 4,6,7 although Oscier et al showed that oral administration may allow for better analgesia 8,9 . Additionally, acetaminophen is a nonsteroidal anti‐inflammatory drug that can reduce the incidence of postoperative nausea and vomiting (PONV) by affecting several serotonergic pathways in the central nervous system 10,11 .…”
Section: Introductionmentioning
confidence: 99%